Analysis of Intra-Algeria-Tunisia Trade Performance Standard Study(2000-2021) - Tarek YALOULI; Fayza JALLOULI; Elhadi LARBAA (Journal of North African Economies, 2025)
This study aimed to analyze the factors affecting the performance of intra-trade between Algeria and Tunisia, based on data from the World Bank for Algeria and Tunisia during the period (2000-2021). The impact of some macroeconomic indicators on the structure of exports and imports of Algeria and Tunisia was measured using the gravity model and the IVOZ program with the panel data analysis approach, where the data of these variables were collected after conducting various necessary tests. The exchange between Algeria and Tunisia negatively affects the exports and imports of the two countries, while the rest of the variables have a positive impact on exports and imports. This necessitates the need for Algeria and Tunisia to pay attention to addressing the problem of the structure of trade products and the mutual exchange rate index, and to reduce its negatives, in exchange for stimulating and encouraging various efforts.